ANALISIS PRODUK UNGGULAN TANAMAN PANGAN DI PROVINSI RIAU - Nani Jayanti; Eriyati -; Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is done/conducted by in Province Riau. The selecting of this area because to know superior product of food crop in Province Riau and To see the level of contribution of subsektor food crop to agricultural sector and agricultural sector contribution in economics of Province RiaU. Type and data source which is used in this research is data of sekunder Time Series, that is obtained from information and also report published by Statistical Body Center of Province Riau, and statistical publication data of indonesia. Result of this research is expected can be of benefit to government of Province Riau expected can be made as input in making policy and execution of development of Province Riau a period of/to to come and upon which information to researchers hereinafter. From result of research obtained by paddy crop represent superior product of food crop in Riau province because seen from result of analysis of LQ got that paddy crop of year 2008 - 2012 having value of LQ > 1 , that is in the year 2008 with value of LQ 1,36512, year 2009 with value of LQ 1,32451, year 2010 value of LQ 1,37013, year 2011 with value of LQ 1,35989, and year 2012 with value of LQ 1,33677. This its meaning of paddy crop represent superior product of food crop of Province Riau.Keywords: Superior Product, Location Quotient, Food Crop